Comparative analysis of activity of coagulation Factors V and VIII and level of fibrinogen in fresh frozen plasma and frozen plasma - Dogra, Mitu (Asian J Transfus Sci, 2015)
BACKGROUND: The aim of this study was to analyse and compare the activity of factor V, VIII and fibrinogen level in fresh frozen plasma and frozen plasma frozen after 8 hrs but within 24 hours after phlebotomy. MATERIALS AND METHODS: Fresh frozen plasma separated from whole blood within 8 hours was compared with plasma separated within 24 hours after phlebotomy in terms of coagulation factors V and VIII and level of fibrinogen by standard methods using semi automated coagulometer sysmex CA50. RESULTS: Longer storage of whole blood before processing resulted in significant decrease (18.4%) in activity of factor VIII but the fall in activity of factor V (6.52%) or level of fibrinogen (1.81%) was not significant. DISCUSSION: These data suggest that there is good retention of coagulation factors in both types of plasma. Although there is significant fall in activity of factor VIII, but it is an acute phase reactant and raised in most of the diseases so it is suggested that frozen plasma would be an acceptable product for most patients requiring fresh frozen plasma.